Implementasi Prinsip-Prinsip Ekowisata di Daya Tarik Wisata Hidden Strawberry Garden Desa Pancasari, Kabupaten Buleleng, Bali - Pratama, Dea; Arida, I Nyoman Sukma (JURNAL DESTINASI PARIWISATA, 2023)
Hidden Strawberry Garden tourist attraction is one of the strawberry farms with a high demand category in Pancasari Village, Buleleng Regency. As one form of alternative tourism Hidden Strawberry Garden promotes the concept of Agro-ecotourism and development that leads to sustainable agricultural. This research seeks to analyze the implementation of ecotourism principles that have been implemented or applied by the owner of Hidden Strawberry Garden tourist attraction and tourist activities offered to tourists. The implementation of ecotourism principles was analyzed using the principles of ecotourism according to Donohoe and Needham (2006) and tourism activities were analyzed with the concept of tourism activity 4S. This research used qualitative approach with data collection methods through observation, interviews, and literature study. The results showed that tourism activities that can be carried out by tourists lead to cultivated land plantation activities including; strawberry picking, organic farming and gardening, and enjoying green scenery. While the implementation of the principles of ecotourism there are six indicators such as, nature-based, preservation/conservation, environmental education, sustainability, benefit distribution, and ethics/responsibility have not been implemented optimally by the manager so that based on the ecotourism spectrum Hidden Strawberry Garden is classified into pseudo ecotourism, which is ecotourism "lite". Keywords: Implementation, Ecotourism, Hidden Strawberry Garden, Pancasari Vllage